The problem of transaction processing using microservice architecture - Fomin, D.S.; Bal'zamov, A.V. (Известия высших учебных заведений. Поволжский регион:Технические науки, 2021)
Background. The object of the research is an e-commerce system built on the principle of microservice architecture. The subject of the research is methods of ensuring correct operation of transactions using a microservice architecture. The purpose of the work is to find an optimal method for solving the problem of processing transactions using a microservice architecture. Materials and methods. Research was carried out in the field of architectural solutions for the construction of high-load e-commerce systems. T Two-phase commit methods were used to process transactions and a pattern-compensating transaction − “Saga”. Results. The research analyzes the features of working with transactions and proposes methods for solving the problem of processing transactions in systems built using a microservice architecture. Conclusions. The approaches considered, as a rule, involve the introduction of additional services (Transaction Coordinator or Saga Orchestrator) that manage the life cycle of transactions, which increases development costs and complexity. Applying the described solution methods, the system becomes more fault-tolerant and scalable.